PERBANDINGAN KETERAMPILAN KOMUNIKASI DAN KEMAMPUAN PENGUASAAN KONSEP SISWA MELALUI PEMBELAJARAN VIRTUAL MENGGUNAKAN GOOGLE CLASSROOM DAN PEMBELAJARAN MENGGUNAKAN WHATSAPP - Navisha Armya Hazqil, - (2020)
This study aims to analyze the communication skills of High School student between learning environmental material using Google Classroom and by learning using WhatsApp. The participant in this study were student of SMAN 11 Bandung with X MIPA 1 using Google Classroom application and X MIPA 4 using learning by WhatsApp application. The communication skills were analyzed based on K - 12 Public Education 21st century skills and the ability of cognitive based on bloom taxsonomy. The data was collected communication by observing and documentaring from student activities using Google Classroom application and using WhatsApp application, and for collected cogtinif data by pretest and posttest about environmental material. The result of this study obtained the communication skills of student's there is a significant difference between using Google Classroom and by learning using WhatsApp based on statistic T test. The result ability cogtinif of student's not is a significant difference between using Google Classroom and by learning using WhatsApp based on statistic Mann - Whitney Test. This means that the Google Classroom application is only able to develop and awaken students in communication skills, and build 21st century communication skills. Keywords : Education, 21st Century Communication Skills, Virtual Classroom, Google Classroom, Whatsapp, Environmental Damage